TOURISM INTEREST AND THE EFFICIENCY OF ITS UTILISATIONS BASED ON THE EXAMPLE OF THE EU COUNTRIES - Kosmaczewska, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2014)
This article discusses the subject of the efficiency of the transformation of tourism interest defined as arrivals in tourist accommodation establishments into outputs, such as collective tourist accommodation establishments and GDP per inhabitant in the EU countries. For the measurement of efficiency the DEA method was used and the following models were assumed: CCR, BCC, NIRS. As a result was confirmed that significant similarity in the efficiency of the transformation of the inputs above referred to into outputs was only observed in the group of richer countries (GDP > average for the EU) or in the group of poorer countries. The analysis conducted proved that richer countries achieved higher PTE, while poorer countries achieved higher SE.